Coronary thromboembolic acute myocardial infarction due to paroxysmal atrial fibrillation occurring after non-cardiac surgery. (26th March 2015) - OSullivan, Crochan John; Sprenger, Martin; Tueller, David; Eberli, Franz Robert
Abstract : Acute myocardial infarction is a well know precipitant of atrial fibrillation, but it is also becoming increasingly recognised that atrial fibrillation is a direct and indirect cause of acute myocardial infarction. Current guidelines do not recommend anticoagulation therapy in patients undergoing cardiac surgery who have a brief episode of atrial fibrillation lasting less than 48 h. However, recommendations for the management of atrial fibrillation following non-cardiac surgery are less clear. We describe the case of a 70-year-old man undergoing non-cardiac surgery, who developed a short episode of perioperative atrial fibrillation and later presented with thromboembolic acute myocardial infarction due to a thrombotic occlusion of the right coronary artery.